Genetic Analysis and Preliminary Mapping of a Highly Male-Sterile Gene in Foxtail Millet (Setaria italica L. Beauv.) Using SSR Markers - Jun WANG; Zhi-lan WANG; Hui-qing YANG; Feng YUAN; Er-hu GUO; Gang TIAN; Yuan-huai AN; Hui-xia LI; Yu-wen WANG; Xian-min DIAO; Ping-yi GUO (Journal of Integrative Agriculture)
Breeding of male-sterile lines has become the mainstream for the heterosis utilization in foxtail millet, but the genetic basis of most male-sterile lines used for the hybrid is still an area to be elucidated. In this study, a highly male-sterile line Gao146A was investigated. Genetic analysis indicated that the highly male-sterile phenotype was controlled by a single recessive gene a single recessive gene. Using F2 population derived from cross Gao146A/K103, one gene controlling the highly male-sterility, tentatively named as ms1, which linked to SSR marker b234 with genetic distance of 16.7 cM, was mapped on the chromosome VI. These results not only laid the foundation for fine mapping of this highly male-sterile gene, but also helped to accelerate the improvement of highly male-sterile lines by using molecular marker assisted breeding method.